EXPERIENCE OF DELIVERING WOMEN USING VACUUM FETAL EXTRACTION SURGERY - Елена Николаевна Кравченко; Софья Сергеевна Синицына; Лариса Владимировна Куклина; Наталья Григорьевна Муравьева; Галина Анатольевна Алехно (The Publishing House Medicine and Enlightenment, 2021)
Purpose of the study - analysis of obstetric and perinatal labor outcomes using operative vaginal delivery using vacuum extraction of the fetus. Materials and methods. A study was carried out, consisting in a retrospective analysis of 290 birth histories of women who were delivered using the vacuum extraction of the fetus using the KIWI system over the past 3 years (2018-2020). This amounted to 2.0 % of all delivered deliveries during the analyzed period of time. Results. The operation of vacuum extraction was carried out for acute fetal hypoxia in 72.4 % of cases, and due to weakness of labor forces - in 27.6 % of cases. The Apgar score of 7-8 points was confirmed in the bulk of infants (280 children - 96.6 %), the condition was assessed at 6-7 points in 7 newborns (2.4 %), 4-5 points - in 3 (1,0 %), while resuscitation care was required for 2 children (0.7 %). Conclusion. Vacuum extraction of the fetus is a safe vaginal operation for the mother and the fetus, subject to strict adherence to the conditions for its implementation, correct assessment of contraindications and proper technique.